2021
DOI: 10.1016/j.rmed.2021.106648
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory rehabilitation for Covid-19 related persistent dyspnoea: A one-year experience

Abstract: Background Growing consideration is emerging regarding the burden of persisting sequelae after SARS-CoV-2 infection. Out-patients exhibiting long Covid may benefit from ambulatory rehabilitation which is, to date, poorly documented. Methods A longitudinal follow-up over a one-year period was conducted in two ambulatory rehabilitation structures in order to describe the characteristics of real-life patients referred with Covid-19 sequelae and their evolution over the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
2
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 43 publications
5
53
2
7
Order By: Relevance
“…In our study, while dyspnea (mMRC) and FEV 1 were improved by 1.79 points and 110 ml, respectively, HGS remained unchanged (Table 2). The finding related to dyspnea is in line with previous reports (Table 4) indicating that CRRP improves perceived dyspnea [whatever its mode of evaluation; e.g., mMRC (Bouteleux et al, 2021;Gloeckl et al, 2021), chronic obstructive pulmonary disease assessment test (Daynes et al, 2021)], even in severe/critical COVID19 patients (Gloeckl et al, 2021). In our study, mMRC improvement was higher than the one point MCID (Crisafulli and Clini, 2010).…”
Section: Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, while dyspnea (mMRC) and FEV 1 were improved by 1.79 points and 110 ml, respectively, HGS remained unchanged (Table 2). The finding related to dyspnea is in line with previous reports (Table 4) indicating that CRRP improves perceived dyspnea [whatever its mode of evaluation; e.g., mMRC (Bouteleux et al, 2021;Gloeckl et al, 2021), chronic obstructive pulmonary disease assessment test (Daynes et al, 2021)], even in severe/critical COVID19 patients (Gloeckl et al, 2021). In our study, mMRC improvement was higher than the one point MCID (Crisafulli and Clini, 2010).…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…Our results concerning spirometry data are comparable with those investigating the impact of CRRP on lung function data (Liu K. et al, 2020;Bouteleux et al, 2021;Gloeckl et al, 2021;Puchner et al, 2021) (Tables 4, 5). In the latter studies, at least one lung function parameter was improved [FEV 1 (Liu K. et al, 2020;Gloeckl et al, 2021;Puchner et al, 2021), FVC (Liu K. et al, 2020;Bouteleux et al, 2021;Gloeckl et al, 2021;Puchner et al, 2021), total lung capacity (Puchner et al, 2021), diffusing lung capacity for carbon monoxide (DLCO) (Liu K. et al, 2020;Puchner et al, 2021)]. Concerning the improvement in FEV 1 , the 110-ml increase observed in our study was lower than the values reported in the literature [e.g., 200 ml (Puchner et al, 2021), 340 ml (Liu K. et al, 2020)].…”
Section: Discussion Of Resultssupporting
confidence: 90%
“…Wood et al (2021) also reported low levels of end-tidal carbon dioxide despite normal respiratory rate in individuals with long COVID. In our study, a one-month rehabilitation program at hospital or in community-based center showed an improvement in the majority of parameters of hyperventilation syndrome; which was also found in patients with persistent symptoms after a COVID-19 infection and who underwent a respiratory rehabilitation program (Bouteleux et al, 2021). However, we note nevertheless that the values remained below the thresholds of good prognosis in our sample.…”
Section: Discussionsupporting
confidence: 59%
“…Currently, the data on the effects of COVID-19 are growing rapidly. These data suggested that even if COVID-19 patients fully recover, they may face the risk of a variety of mid- and long-term effects [ 60 ]. Our systematic review and meta-analysis of 40 cohort studies involving 10,945 cases of SARS-CoV-2 infection provide the pooled prevalence (PP) of long-term consequences of COVID-19 at 6 months and above, and we compared subgroups stratified by follow-up period, severity of COVID-19, and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Available data analyses have shown that respiratory symptoms were common in long COVID-19, and a high PP of persistent dyspnea is of concern. A French study found that hyperventilation syndrome was common in COVID-19 patients (34%) [ 60 ], which may be related to the occurrence of persistent dyspnea. People with COVID-19 could suffer from varying degrees of respiratory damage.…”
Section: Discussionmentioning
confidence: 99%